STRATEGI PENGEMBANGAN PARIWISATABERBASIS BUDAYA SEBAGAI DAYA TARIK DI DESA LENEK LOMBOK TIMUR - Rifqi Agung Samudra; I Ketut Bagiastra; I Made Suyasa (Program Studi S1 Pariwisata, Sekolah Tinggi Pariwisata Mataram, 2023)
Lenek Village is one of the villages in East Lombok Regency which is designated as a Tourism Village in West Nusa Tenggara Province. The development of culture-based tourism in this village is expected to provide benefits to the community if it is managed properly and planned. This study aims to obtain recommendations for a strategic plan for the development of culture-based tourism in Lenek village. The analytical method used in this study includes interpretive qualitative descriptive analysis assisted by the SWOT analysis method to determine the development strategy plan. The results show that the priority of the strategic plan for developing culture-based tourism in Lenek village is to develop tourism products in the form of traditions and arts that are still routinely carried out by the local community and have high interest from tourists such as the Ngejot Tradition, Presean, Gagak Mandik Dance, Dara Ngindang Dance, and Pidata Dance as well as by improving management, marketing, and collaboration between the community and the local village government.